1998
DOI: 10.1016/s0375-9474(98)00562-4
|View full text |Cite
|
Sign up to set email alerts
|

Translationally invariant treatment of pair correlations in nuclei II. Tensor correlations

Abstract: We study the extension of our translationally invariant treatment of few-body nuclear systems to include tensor forces and correlations. It is shown that a direct application of our method is not as successful for realistic V6 interactions as our previous results for V4 potentials suggested. We investigate the cause in detail for the case of 4 He, and show that a combination of our method with that of Jastrowcorrelated wave functions seems to be a lot more powerful, thereby suggesting that for mildly to strong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…It has been shown that this kind of wavefunction is a good approximation to describe light systems such as 4 He [1,5]. The results are rather close to the most accurate results, obtained by using a Green function Monte Carlo [6] or variational approach with a state-dependent Jastrow correlation [7].…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…It has been shown that this kind of wavefunction is a good approximation to describe light systems such as 4 He [1,5]. The results are rather close to the most accurate results, obtained by using a Green function Monte Carlo [6] or variational approach with a state-dependent Jastrow correlation [7].…”
Section: Introductionsupporting
confidence: 71%
“…The effects obtained for the other nuclei are quite similar and thus have not been shown explicitly. A general trend for these nuclei and/or potential is the small magnitude of ρ (1) LO,L (r) and the resemblance between ρ (1) J L,L (r) and ρ (1) J LO,LO (r). These facts indicate that, in spite of their relevance to the binding energy of the system, the state-dependent correlations hardly affect the nuclear density.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…[24,25] for additional information), further applications to nuclear structure calculations based on realistic nuclear interactions proved difficult to *Electronic address: bmihaila@lanl.gov achieve. In 1990s we mainly note the attempt of constructing a translationally invariant CCE in coordinate space [26][27][28], method which might yet offer an attractive alternative for finite nuclei calculations (see Refs. [29,30] for information on recent progress on this approach.)…”
Section: Introductionmentioning
confidence: 99%